Management and leadership in the 4th industrial revolution : capabilities to achieve superior performance - Wyatt, Stephen (New York : Kogan Page Ltd, 2020)
'The business world is currently experiencing fundamental disruption, in part driven by the technology enabled Fourth Industrial Revolution. Corporate value is created and lost in breathtakingly short periods, and the rise of'unicorns' against the demise of once-venerated organizations has shown that how firms compete has changed. Management and Leadership in the 4th Industrial Revolution presents a framework for managing and winning in the new accelerated world of business, focusing on the key capabilities organizations now need to achieve competitively superior performance. Building on the'dynamic capabilities' approach already familiar to strategists and based around his own research, Stephen Wyatt shows how executives can assess the dynamic capacity of their organization - a leading indicator of future performance in comparison to their industry peers. Written in an accessible style with best practice examples from companies and quotes from executives to support each insight, this book includes a self-assessment questionnaire to measure the dynamic capacity of your organization and advice on how to strengthen areas of relative weakness. Management and Leadership in the 4th Industrial Revolution offers timely insights on driving innovation and emphasizes the importance of long-term strategy, change management and new models of dynamic leadership'--
Includes bibliographical references and index.
Keywords: Industrial management; Strategic planning; Teams in the workplace -- Management; Organizational change; Organizational effectiveness